PENGARUH HARGA, CITRA MEREK, DAN KEPERCAYAAN KONSUMEN TERHADAP LOYALITAS PELANGGAN KOPI KENANGAN - Rosita, Rahmi; Darlin, Evalina (JURNAL LENTERA BISNIS, 2026)
The research aims to reveal and analyze influence of price perceptioan, brand image and trust on customer loyalty to memorable coffee products. This research method uses data obtained from questionnairres, analyze using descriptive statistical methods. Descriptive analysis is used to describe the caracteristics of respondents and the tendencies of answers to each variable. Using quantitative statistical methods and SPSS tools. Respondents totaled 100 respondents, using incidental sampling technique. The research results show that the influence of priceperception is not significant, but brand image and consumer trust are significant.